2020
DOI: 10.3390/ijerph17218039
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary Reduction of Social Interaction during the COVID-19 Pandemic in Taiwan: Related Factors and Association with Perceived Social Support

Abstract: This study aimed to determine the proportion of individuals who voluntarily reduced interaction with their family members, friends, and colleagues or classmates to avoid coronavirus disease 2019 (COVID-19) infection and the associations of reduced social interaction with perceived social support during the COVID-19 pandemic in Taiwan. Moreover, the related factors of voluntary reduction of social interaction were examined. We recruited participants via a Facebook advertisement. We determined the reduced social… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 44 publications
(50 reference statements)
1
26
0
Order By: Relevance
“…Similarly, we found that social contacts in the shift camps outside of work hours contributed to disease spread. People still interact outside of working hours, and they need targeted communication messages that do not prohibit social interactions, but instead suggest ways to safely telecommunicate or interact with peers in-person [ 41 ]. Indoor interactions with each other should be made safer by improved air disinfection engineering strategies like mechanical ventilation or upper room germicidal ultraviolet air disinfection (GUV).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, we found that social contacts in the shift camps outside of work hours contributed to disease spread. People still interact outside of working hours, and they need targeted communication messages that do not prohibit social interactions, but instead suggest ways to safely telecommunicate or interact with peers in-person [ 41 ]. Indoor interactions with each other should be made safer by improved air disinfection engineering strategies like mechanical ventilation or upper room germicidal ultraviolet air disinfection (GUV).…”
Section: Discussionmentioning
confidence: 99%
“…The reciprocal relationship between annual leave being frozen and lowered social relationship QoL could be deduced from the decreased ability to engage in social relationships resulting from a lack of time for interaction with family and social circle of healthcare workers because of longer working hours during the pandemic. In addition, a reduction in social interaction with classmates and family members has been reported in response to the COVID-19 pandemic beyond the social distancing implemented to curb the spread of the infection (Chou et al, 2020). The impact of depression and stress on social functioning is well documented, and increased severity of stress and depression may have further aggravated social functional impairment during the COVID-19 pandemic (Kupferberg et al, 2016;Gallagher et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Patients may also have lesser community-based support due to the suspension of social services. 8 Indeed, a recent World Health Organization survey of 134 countries shows that the pandemic had a profound impact on the delivery of health care, with services for chronic care and psychosocial services severely compromised in at least 44% of the countries studied. 9 Experiencing delays in much-needed diagnostics, therapeutics, and surgeries could have dire consequences for patients with underlying chronic conditions.…”
mentioning
confidence: 99%